Implementasi Peraturan Bupati Kuantan Singingi Nomor 3 Tahun 2012 Tentang Ketentuan Jam Kerja Bagi PNS dan Non PNS Dilingkungan Pemerintah Kabupaten Kuantan Singingi - Risvandi Risvandi (Mathematics Education Study Program, 2025)
Local governance as a subsystem of state government do to improve the effectivenessand efficieney of government administration and service to the community. Smoothness of governance and implementation of national development mainly depends on the perfection of civil servants. Smoothness of the task of governance and national development, especially in the era of regional autonomy depends on the perfection of the state apparatus, especially civil servants, in order to achieve the national development goals that embody civil society law-abiding, civilized modern, democratic, prosperous, just and virtuous required employee countries that are the state apparatus who served as a public servant, in practice, Indonesian Civil Servants in general are still many shortcomings that less follow the rules of employee discipline, which can hamper the smooth governance and national development Based on this, the Indonesian Civil Servants seen many shortcomings the lack of respect the time, effort and discipline streamline work. The purpose of this study is to investigate and presenting implementation Kuantan Singingi decree No. 3 of 2012 Hours neighbor Conditions for Civil Service and non-Civil Servants Regeney Kuantan Singing within the government, and explains the constraints. The conclusion of this study that the implementation of the decree No. 3 Kuantan Singing 2012 About provisions Hours For Civil Service and non-Civil Servants seen from the communication indicator, regulatory submission regent, clarity of obligations and prohibitions, consistent with the implementation of the apple, consistent with penalties for violations, resources, understanding the rules Kuantan Singingi decree No. 3 of 2012, the disposition attitude, responsibility and motivation are lacking in implementing discipline, lack of supervision and bureaucratic structures, the structural development of officials from each field, still less implemented correctly.